2012
DOI: 10.1073/pnas.1116125109
|View full text |Cite
|
Sign up to set email alerts
|

Induction of microRNA-155 is TLR- and type IV secretion system-dependent in macrophages and inhibits DNA-damage induced apoptosis

Abstract: Helicobacter pylori is a gastric pathogen responsible for a high disease burden worldwide. Deregulated inflammatory responses, possibly involving macrophages, are implicated in H. pylori-induced pathology, and microRNAs, such as miR-155, have recently emerged as crucial regulators of innate immunity and inflammatory responses. miR-155 is regulated by Toll-like receptor (TLR) ligands in monocyte-derived cells and has been shown to be induced in macrophages during H. pylori infection. Here, we investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 81 publications
2
77
1
Order By: Relevance
“…Recent research demonstrated that miR-155 was found to be induced by diverse TLR ligands through the NF-κB signaling pathways (49). In our study, we found that S100A8 upregulated the expression of miR-155 in a time-dependent manner in the inflammatory microenvironment.…”
Section: Discussionsupporting
confidence: 58%
“…Recent research demonstrated that miR-155 was found to be induced by diverse TLR ligands through the NF-κB signaling pathways (49). In our study, we found that S100A8 upregulated the expression of miR-155 in a time-dependent manner in the inflammatory microenvironment.…”
Section: Discussionsupporting
confidence: 58%
“…S6A). Consistent with this hypothesis, a recent study suggested that miR-155 protects macrophages from apoptosis through its regulation of multiple proapoptotic genes, including Noxa (30). Although Noxa mRNA levels did not differ greatly in WT and miR-155 −/− NK cells after viral infection, miR-155-mediated suppression of Noxa, in addition to numerous other gene targets, may still be a contributing factor to the preferential expansion and memory maintenance of WT compared with miR-155 −/− or Noxa-expressing NK cells observed after MCMV infection.…”
Section: Discussionsupporting
confidence: 50%
“…Upregulation of BCL6 in lesional Mir155 -/-macrophages repressed CCL2 expression, which is known to promote the recruitment of monocytes to atherosclerotic plaques (18). In addition to its immunoregulatory functions, miR-155 can enhance or prevent the apoptosis of infected macrophages (52,53). However, we did not observe any effect of miR-155 on the apoptosis of lesional macrophages.…”
Section: Discussioncontrasting
confidence: 50%